Evaluation of the Therapeutic Effectiveness of the “Thuoc an than Ba Giang” Hard Capsules in the Treatment of Insomnia - Van Vi, Nguyen; Duc Hanh, Le Thi; Quang Thao, Le; Cao Son, Doan; Duy Bac, Nguyen; Thi Lien, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
The “Thuoc an than Ba Giang” hard capsules (ATBG) have previously been evaluated for preclinical safety. In the present study, the drug's clinical safety and efficacy in treating insomnia were further investigated using a prospective, open-label, before-and-after intervention design without a control group. The results show that after 30 days of treatment, ATBG increased patients’ total sleep time from 3.04 ± 0.5 to 5.92 ± 0.45 hours; sleep onset latency decreased from 74.87 ± 10.73 to 29.12 ± 9.13 minutes; and sleep efficiency improved from 43.48 ± 7.14% to 73.23 ± 5.99%. Patients’ sleep quality also improved, with an increase in the proportion of fair and good sleep quality and a reduction in the proportion of poor and average sleep quality. The rate of marked improvement according to the ISI scale was 45.7%, and the rate of no improvement was 0.0%. No clinical adverse effects or abnormal paraclinical findings were observed. These results indicate that ATBG is effective in the treatment of insomnia without causing adverse effects in patients.